2012
DOI: 10.1007/s11434-012-5179-y
|View full text |Cite
|
Sign up to set email alerts
|

MHC polymorphism and disease-resistance to Edwardsiella tarda in six turbot (Scophthalmus maximus) families

Abstract: This study examined genetic variation in the major histocompatibility complex (MHC) Class II B gene in turbot (Scophthalmus maximus) by virulent bacterial pathogen challenge. One hundred fry from each of six families were infected with Edwardsiella tarda by intraperitoneal injection. Family mortality ranged from 28.0% to 83.3%. Complete exon 2 and intron 1 sequences of MHC Class II B genes were amplified from five survivor and five non-survivor individuals per family using the clone-sequence method. Thirty-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Genomic DNA was isolated from fin tissues of each animal, using the phenol-chloroform method described by Du et al (2012). Following extraction, DNA samples were diluted to 100 µg/µL and stored at -20ºC until further use.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated from fin tissues of each animal, using the phenol-chloroform method described by Du et al (2012). Following extraction, DNA samples were diluted to 100 µg/µL and stored at -20ºC until further use.…”
Section: Methodsmentioning
confidence: 99%
“…; Du et al . ) respectively. Furthermore, we detected high polymorphism quantity parameters ( K = 16.357, Pi = 0.065).…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, numerous studies concerning the association between MHC gene polymorphisms and disease resistance have been reported in fish (Zhang, Chen, Liu, Sha & Liu ; Croisetie`re, Tarte, Bernatchez & Belhumeur ; Xu, Chen, Ji & Tian ; Rakus, Wiegertjes, Jurecka, Walker, Pilarczyk & Irnazarow ; Xu, Chen & Zhang ; Li, Liu, Zhao, Ma, Feng & Wang ; Du, Chen, Liu, Niu, Yang & Zhang ). Rainbow trout ( Oncorhynchus mykiss ) are a cold‐water fish that are widely cultured in the global market and have high economic value.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers encoding disease-resistant characters have been studied in a number of aquaculture species. Allele-specific major histocompatibility complex (MHC) II correlates with disease resistance in tilapia (Zhou et al, 2013), goldfish (Hayuningtyas et al, 2013), rainbow trout (Dijkstra et al, 2013), Chinese long snout catfish (Shen et al, 2011), turbot Scophthalmus maximus (Du et al, 2012), Catfish (Alimuddin et al, 2018), and three-spined fish sticklebacks (Gasterosteus aculeatus) (Consuegra & de Leaniz, 2008;Kurtz et al, 2006;Wegner et al, 2006). It is also reported that there is a close relationship between MHC gene variation and resistance traits, such as in Atlantic salmon Salmo salar (Landry & Bernatchez, 2002), sockeye salmon, Oncorhynchus nelka (Miller et al, 2001).…”
Section: Introductionmentioning
confidence: 99%